Overexpression of Chicken IRF7 Increased Viral Replication and Programmed Cell Death to the Avian Influenza Virus Infection Through TGF-Beta/FoxO Signaling Axis in DF-1 - Kim, Tae Hyun; Zhou, Huaijun (Frontiers in Genetics, 2018)
During mammalian viral infections, interferon regulatory factor 7 (IRF7) partners with IRF3 to regulate the type I interferon response. In chickens, however, it is still unclear how IRF7 functions in the host innate immune response, especially given that IRF3 is absent. To further elucidate the functional role of chicken IRF7 during avian influenza virus (AIV) infection, we generated inducible IRF7 overexpression DF-1 cell lines and performed in vitro infection using low pathogenic AIVs (LPAIVs). Overexpression of IRF7 resulted in higher viral replication of H6N2 and H10N7 LPAIVs compared to empty vector control cells regardless of IRF7 expression level. In addition, a high rate of induced cell death was observed due to elevated level of IRF7 upon viral infection. RNA-seq and subsequent transcriptome analysis of IRF7 overexpression and control cells discovered candidate genes possibly controlled by chicken IRF7. Functional annotation revealed potential pathways modulated by IRF7 such as TGF-beta signaling pathway, FoxO signaling pathway and cell structural integrity related pathways. Next, we analyzed the host response alteration due to the IRF7 overexpression and additionally discovered the possible connection of chicken IRF7 and JAK-STAT signaling pathway. These findings suggest that chicken IRF7 could modulate a wide range of cellular processes in the host innate immune response thus meticulous control of IRF7 expression is crucial to the host in response to AIV infection.